Unconventional secretion of the autophagy-related protein VMP1 via extracellular vesicles as a potential biomarker for pancreatic cell injury - Tadic, Mariana S. (2024)
Cellular stress activates various mechanisms, including autophagy and vesicular trafficking, to maintain homeostasis and cope with pathological conditions such as acute pancreatitis. One of these mechanisms involves the unconventional secretion of extracellular vesicles (EVs), lipid bilayer-delimited particles released by almost all cell types into the extracellular medium. Recently, an autophagy-related secretory pathway that releases EVs has been discovered. Our study focuses on Vacuole Membrane Protein 1 (VMP1), an autophagy-related protein implicated in pancreatitis, diabetes, pancreatic cancer, and cellular stress management. VMP1 expression triggers autophagy in mammalian cells through its ubiquitination and its direct binding to BECN1. Here, we demonstrate that VMP1 is secreted to the extracellular medium integrated into the membrane of EVs. Using cell lines expressing different VMP1-tag expression plasmids, we successfully isolated and purified VMP1-containing EVs (VMP1-EVs) from the extracellular medium through ultracentrifugation and immune isolation techniques. The secretion of VMP1-EVs was reduced by mTOR inhibition and in the absence of proteins essential for autophagosome formation, such as ATG5. The secretion of endogenous VMP1 by pancreatic acinar cells was highly induced in experimental models of cell stress, including blocked autophagic flux with Bafilomycin and exposure to supramaximal doses of caerulein. Moreover, immuno-isolation of VMP1-EVs from cell models revealed that VMP1 is a component of EV membranes. Transmission electron microscopy (TEM) and dynamic light scattering (DLS) analysis of immuno-isolated VMP1-EVs indicated a diameter of around 150 nm. Western blot assay demonstrated that the autophagy related protein LC3-II and p62 are co-secreted with VMP1 in cellular stress models. Furthermore, VMP1-EVs are taken up by different host cells, suggesting that VMP1-EVs may be able to mediate remote communication between cells. In conclusion, we have demonstrated for the first time that the pancreatitis-associated transmembrane protein VMP1 is unconventionally secreted as a component of extracellular vesicles via a secretory autophagy pathway.